The effect of fatiguing muscle contractions on kicking performance in experienced soccer players - Carstensen, J. B.; Gaemelke, T.; Overgaard, K.; Andersen, T. B. (Sports Biomechanics, 2024)
The objective of this study was to clarify the effects of fatiguing muscle contractions of the m. quadriceps femoris on kicking abilities of experienced soccer players. 16 male professional (n = 5) and amateur players (n = 11) performed kicking tests in two conditions (fatigue and control) on separate days in a randomised crossover design. The fatiguing protocol performed with the kicking leg consisted of 5 sets of 10 maximal voluntary concentric and eccentric knee extensions. Maximal voluntary isometric contraction force (MVIC), 15 hz/50 hz stimulation force ratio (force ratio), and kicking abilities were assessed before and after completion of the fatiguing protocol or rest (control). The fatiguing protocol successfully induced fatigue of 14.0 ± 2.7% (mean ± SE) reduced MVIC and 14.0 ± 3.7% reduced force ratio while no reductions occurred in the control condition. Between group difference showed ball speed declined 2.1 ± 0.95% more following the fatigue protocol compared to control condition. On the control day shooting accuracy improved by 13.3 ± 5.6% and was numerically impaired on the intervention day by 1.0 ± 9.2%. Despite this, no significant between group difference was observed in shooting accuracy (p = 0.18). The study demonstrated that fatigue induced by prior muscle contractions impairs maximal shooting speed, but we observed no significant impairment of shooting accuracy.